Evolução da paisagem e ocorrência de Latossolos húmicos nos Brejos de Altitude da Paraíba - Marques, Ailson de Lima (2019)
The Brejos de Altitude (Mountains) are exception areas in the Borborema plateau in northeastern Brazil. It occurs in the middle of the semi-arid climate and has differentiated climatic conditions from the surroundings, where temperatures are milder and higher humidity, conditioning the establishment of Forest islands. Ombrophils (Atlantic Forest) and more developed soils with higher organic matter content than the soils in the surrounding areas. In the Borborema Plateau, Xantic Ferralsols and humic A horizon occur in the altitude swamps (altimontano environment) in the Serra dos Martins Formation, which constitute the only Cenozoic planing remnant still preserved. The occurrence of Ferralsols with humic A is still little explained by the current literature, and in Brejos de Altitude there are records of occurrence only in Brejão and Pau D´alho in Pernambuco state, and Areia in Paraíba state. In Paraíba, this rare soil can be considered a relictual paleosol. In this sense, this study investigated the evolution of the landscape and its distribution of soil classes, with emphasis on the occurrence of the humic Ferralsols. The humic horizon A often very thick and with low base saturation, where lower temperatures, typical of the windward position with higher humidity, favored the ferratilization process with formation of this horizon, with accumulation of organic matter to depths greater than 100 cm. Among the methods used to analyze these soils are morphological, chemical and physical analysis, C and N isotopes and phytolites. Thus, they also perform ecosystem services and remain in the current landscape due to the encapsulation of relief and the protection of organic matter, related to factors intrinsic to the soil and the environment, such as the formation of stable organo-mineral complexes. This higher amount of organic matter resulted, therefore, from several environmental factors, which through multiproxies (phytoliths, isotopes and dating), include current climate variables (temperature and precipitation), vegetation type, paleofires and geographic position. There is a response of the degree of pedogenesis to the climatic gradient, where the Humic Ferralsol found in Areia is dated to 6,150 years (14C). This gradient also reflects the diversity and quantity of phytoliths. Soils store organic carbon in the range of 700 Gt. There is a need to assess the importance of coals in all profiles, and see if paleofires were part of the genesis of these soils.